1997
DOI: 10.1577/1548-8675(1997)017<1158:saroef>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Status and Risk of Extinction for Westslope Cutthroat Trout in the Upper Missouri River Basin, Montana

Abstract: Westslope cutthroat trout Oncorhynchus clarki lewisi now occupy less than 5% of the subspecies' historical range within the upper Missouri River drainage in Montana. We assessed the risk of extinction for 144 known populations inhabiting streams within federally managed lands in the upper Missouri River basin using a Bayesian viability assessment procedure that estimates probability of persistence based on subjective evaluation of population survival and reproductive rates as influenced by environmental condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 15 publications
2
59
1
Order By: Relevance
“…Many of the remaining non-hybridized populations throughout the range of WCT are restricted to isolated headwaters (Shepard et al 1997;Mayhood 1999;Hilderbrand and Kershner 2000), and non-hybridized populations in the upper Kootenay River drainage seem to be no exception. All five localities with no evidence of introgression with RBT are located on tributaries further upstream from the mainstem upper Kootenay River than their hybridized counterparts.…”
Section: Geographic and Temporal Trends In Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the remaining non-hybridized populations throughout the range of WCT are restricted to isolated headwaters (Shepard et al 1997;Mayhood 1999;Hilderbrand and Kershner 2000), and non-hybridized populations in the upper Kootenay River drainage seem to be no exception. All five localities with no evidence of introgression with RBT are located on tributaries further upstream from the mainstem upper Kootenay River than their hybridized counterparts.…”
Section: Geographic and Temporal Trends In Hybridizationmentioning
confidence: 99%
“…There are also disjunct populations in Washington State, Oregon and in the South Thompson River (Fraser River drainage), Columbia River and Kettle River in BC. There have been significant declines in WCT populations throughout their historic distribution due to habitat loss and degradation, overexploitation, competition and predation by non-native salmonids, and introgressive hybridization with introduced rainbow trout (RBT, O. mykiss) and Yellowstone cutthroat trout (YCT, O. clarki bouvieri; Allendorf and Leary 1988;Liknes and Graham 1988;Shepard et al 1997). WCT are currently blue-listed in BC (i.e., species of special concern) and under review for a federal listing under the Canadian Species at Risk Act (SARA).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Shepard et al (1997) estimated that westslope cutthroat trout of at least 90 percent genetic purity presently inhabit less than 3 percent of the former range within the upper Missouri River drainage, which has long been regarded as the heart or core of this subspecies' historic distribution (Behnke 1992). Of 16 upper Missouri subbasins still supporting at least one population, 14 contain populations at moderate or high estimated risk of extinction, and almost all of these remaining populations exist in isolation from one another in high elevation mountainous stream fragments less than 10 km long.…”
Section: Similarities With Missouri River Basin Westslope Cutthroat Pmentioning
confidence: 99%
“…Of 16 upper Missouri subbasins still supporting at least one population, 14 contain populations at moderate or high estimated risk of extinction, and almost all of these remaining populations exist in isolation from one another in high elevation mountainous stream fragments less than 10 km long. Shepard et al (1997) identified existing and future land use activities and introduced species as the principal threats to these upper Missouri populations…”
Section: Similarities With Missouri River Basin Westslope Cutthroat Pmentioning
confidence: 99%
See 1 more Smart Citation